Enhancing repurchase intention in e-commerce live streaming via relational bonds during covid-19 pandemic - Yeh, Jia Yee (2022)
The features on e-commerce marketplace are changing dynamically to attract the consumers needs and wants. The embedment of live streaming feature was seeing a profitable future in China e-commerce retail market. However, e-commerce live streaming in Malaysia remains at its infant stage and underrepresented by the previous literature study. This study examined influential factors in repurchase intention via consumer satisfaction and consumer engagement from relationship marketing perspective using StimulusOrganism-Response model. This study sought to close the research gap by examining (1) the influence of financial bond towards consumer satisfaction and consumer engagement, (2) the influence of social bond towards consumer satisfaction and consumer engagement, (3) the influence of structural bond towards consumer satisfaction and consumer engagement and (4) the influence of consumer satisfaction and consumer engagement towards repurchase intention. There were eight hypotheses proposed and examined through quantitative metric using online survey questionnaire. There were 208 valid responses adopted from the survey. All collected data were analysed using Partial Least Square Structural Equation Modelling (PLS-SEM) for inferential analysis. The results of the study provided important findings that financial bond did not significantly influence consumer satisfaction and consumer engagement. Social bond was proven as a stronger predictor in consumer satisfaction, that is, consumers actively seek for care from broadcasters. While structural bond contributed more towards consumer engagement by emphasising valuable information. Proceeding to the repurchase intention, the overall study suggested that consumer satisfaction had greater impact as compared to consumer engagement. The broadcasters, marketers and small-and-medium enterprises who wish to improve sales by generating repeat order from single lead should focus more on making the consumer happy during live streaming.